From Deprivation to Mobilization: Towards a Multideterminant Model of Xenophobic Violence in South Africa - Misago, Jean Pierre (African Human Mobility Review, 2025)
Drawing on extensive and comparative qualitative data from a nearly two-decade long and ongoing research, this article responds to inadequacies and limitations of current causal explanations for xenophobic violence in South Africa. The article argues that existing explanations are inadequate as many lack empirical backing and others are incomplete due to their reductionist approach. To address these shortcomings, this article proposes an empirically based and theoretically informed multideterminant (explanatory) model, which identifies and analyses the roles of—and interconnections between—six key determinants, namely: i) socio-economic and political deprivation, ii) xenophobic beliefs, iii) collective discontent, iv) political economy, v) mobilization, and vi) governance. I argue that i) these determinants and their interconnections in a value-added process constitute the necessary and sufficient conditions for the occurrence of xenophobic violence, and ii) this multideterminant model consequently provides an adequate and comprehensive explanation of the xenophobic violence in South Africa. In addition to its scholarly contribution, this article has potential policy implications. By clearly identifying the key elements in the causal chain, the study implicitly points to critical areas where intervention efforts could be targeted to effectively address the ongoing xenophobic violence in South Africa.